23-gauge pars plana vitrectomy for management of posteriorly dislocated crystalline lens - Cho M (Dove Medical Press, 2011)
Minhee Cho, RV Paul ChanWeill Cornell Medical College, Department of Ophthalmology, New York, NY, USAPurpose: Management of posteriorly dislocated crystalline lens has traditionally been performed with a standard 20-gauge vitrectomy system. This study demonstrates the use of a 23-gauge vitrectomy system for removal of retained lens fragments secondary to spontaneous dislocation or complicated cataract extraction.Methods: A retrospective, noncomparative, interventional consecutive case series at a single university medical center.Results: Fourteen eyes of 14 patients underwent a 23-gauge vitrectomy for removal of retained lens. Mean age was 75 years. Mean logMAR (logarithm of minimum angle of resolution) visual acuity was 1.47 (Snellen equivalent 20/600) preoperatively and 0.37 (Snellen equivalent 20/50) postoperatively. A 20-gauge fragmatome was used in 64% of cases. The mean time to the best post-vitrectomy acuity was 4.9 weeks. The mean healing time was 25 days (6–48 days). Post-vitrectomy complications included choroidal detachment (two patients), vitreous hemorrhage (two patients), and acute ocular hypertension (two patients). The mean length of follow-up was 6.2 months (1–13 months).Conclusion: A 23-gauge vitrectomy system alone or in combination with the 20-gauge fragmatome is a safe and efficacious option for removal of dense posteriorly dislocated crystalline lens material.Keywords: lensectomy, retained lens, PPV